2014
DOI: 10.20870/oeno-one.2014.48.2.1562
|View full text |Cite
|
Sign up to set email alerts
|

SSR molecular marker analysis of the grapevine germplasm of Montenegro

Abstract: <p style="text-align: justify;"><strong>Aim</strong>: Given that the information about the origin, genetic relationships, and diversity of Montenegrin grapevines is still partial, we performed a detailed analysis of the germplasm in this country using simple sequence repeat (SSR) markers. Our main goal was to determine the identity of cultivars unique to Montenegro and those shared with other countries, especially the neighbouring ones.</p><p style="text-align: justify;"><stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In Table 3, SSR markers of identified varieties are presented. Also, all 17 biotypes of Kratošija were confirmed to have the same genetic profile as Zinfandel/Primitivo [33]. According to Maras et al [33] the variety Muškaćela is identical to a variety Muscat bianco-Muscat a petits grains.…”
Section: Genetic Identificationmentioning
confidence: 88%
See 3 more Smart Citations
“…In Table 3, SSR markers of identified varieties are presented. Also, all 17 biotypes of Kratošija were confirmed to have the same genetic profile as Zinfandel/Primitivo [33]. According to Maras et al [33] the variety Muškaćela is identical to a variety Muscat bianco-Muscat a petits grains.…”
Section: Genetic Identificationmentioning
confidence: 88%
“…Also, all 17 biotypes of Kratošija were confirmed to have the same genetic profile as Zinfandel/Primitivo [33]. According to Maras et al [33] the variety Muškaćela is identical to a variety Muscat bianco-Muscat a petits grains. Trojka accession has the same profile as Muscat rouge de Madere (alias Moscato violetto), another important member of the Muscat family.…”
Section: Genetic Identificationmentioning
confidence: 88%
See 2 more Smart Citations
“…According to many literature data, Kratošija cultivar appeared earlier and was introduced into cultivation quite earlier than Vranac (Maraš et al, 2012). Work on autochthonous grapevine cultivars is of huge interest considering the fact that it is shown that Vranac and Kratošija are in close relationship (parent-offspring) and it is proposed that Montenegro is the best candidate for the origin and spreading centre of Kratošija and its group of synonyms (Primitivo, Zinfandel and Crljenak Kaštelanski) (Maraš et al, 2014). Wines of these cultivars are of premium quality, Vranac has dark red ruby colour, full body, fruity taste and pleasant astringency with aging potential in oak barrels.…”
Section: Introductionmentioning
confidence: 99%